\(\text{6+2x=12-4x}\)
<=> 6+2x -12+4x=0
<=> 6x-6=0
<=>6x=6
<=>x=1
\(\text{6+2x=12-4x}\)
<=> 6+2x -12+4x=0
<=> 6x-6=0
<=>6x=6
<=>x=1
-Giải pt :
A. x(x+3)-(2x-1)(x+3)=0
B. 3x-5(x+2)=3(4-2x)
C. (4x-3)(5x-6)=(4x-3)(2x-3)
\(\dfrac{8x^2}{3\left(1-4x^2\right)}=\dfrac{2x}{6x-3}-\dfrac{1+8x}{4+8x}\) giải pt
1) Giải pt bậc nhất 1 ẩn:
a) 1,2 - (x - 0,8)= -2(0,9+x)
b) 2,3x - 2( 0,7+2x)= 3,6 -1,7x
c) 5 - (x - 6)= 4(3 - 2x)
d) 3,6 - 0,5(2x+1)= x - 0,25(2 - 4x)
e) (x - 3) (x + 4) - 2(3x - 2)= (x - 4)\(^2\)
f
giải pt \(\dfrac{13}{\left(x-3\right)\left(2x+7\right)}+\dfrac{1}{2x+7}=\dfrac{6}{x^2-9}\)
Giải phương trình \(\frac{x^2-2x+2}{x-1}+\frac{x^2-8x+20}{x-4}=\frac{x^2-4x+6}{x-2}+\frac{x^2-6x+12}{x-3}\)
Giải pt sau:
\(\frac{x-3}{5}\)=6-\(\frac{1-2x}{3}\)
1) Giải các pt sau:
a) \(\frac{x-3}{5}=6-\frac{1-2x}{3}\)
b) \(\frac{3x-2}{6}-5=\frac{3-2\left(x+7\right)}{4}\)
c) \(\frac{x+8}{6}-\frac{2x-5}{5}=\frac{x-1}{3}-x+7\)
d) \(\frac{7x}{8}-5\left(x-9\right)=\frac{2x+1,5}{6}\)
e) \(\frac{5\left(x-1\right)+2}{6}-\frac{7x-1}{4}=\frac{2\left(2x+1\right)}{7}-5\)
f) \(\frac{x+1}{3}+\frac{3\left(2x+1\right)}{4}=\frac{2x+3\left(x+1\right)}{6}+\frac{7+12x}{12}\)
1.giải các phương trình sau:
A.3x+9=0
B.3x-2=0
C.4-2x=0
D.-2x+6=0
E.0,5x-1=0
F.3,6-0,6x=0
G.2/3x-1=1/3
H.-1/3x+1=2/3x-3
i.4x-3=2x+1
Giải phương trình
1) 16-8x=0
2) 7x+14=0
3) 5-2x=0
4) 3x-5=7
5) 8-3x=6
6) 8=11x+6
7)-9+2x=0
8) 7x+2=0
9) 5x-6=6+2x
10) 10+2x=3x-7
11) 5x-3=16-8x
12)-7-5x=8+9x
13) 18-5x=7+3x
14) 9-7x=-4x+3
15) 11-11x=21-5x
16) 2(-7+3x)=5-(x+2)
17) 5(8+3x)+2(3x-8)=0
18) 3(2x-1)-3x+1=0
19)-4(x-3)=6x+(x-3)
20)-5-(x+3)=2-5x